Comunidad y Estado en Álvaro García Linera Un análisis a través de sus lugares de enunciación (1988-2017) - Torres, Tomás (Ariadna Ediciones, 2018)
Research on the political thought of Alvaro García Linera, his participation in the politics of Bolivia in recent decades